2018
DOI: 10.17323/1814-9545-2018-4-230-260
|View full text |Cite
|
Sign up to set email alerts
|

Third‐Grade Parent’s Involvement in Schools

Abstract: Антипкина Инна Вениаминовна — младший научный сотрудник Центра мониторинга качества образования Национального исследовательского университета «Высшая школа экономики». E-mail: iantipkina@hse.ru Любицкая Кристина Александровна — стажер-исследователь Центра исследований современного детства Национального исследовательского университета «Высшая школа экономики». E-mail: klyubitskaya@hse.ruНисская Анастасия Константиновна — кандидат психологических наук, научный сотрудник Центра исследований современного детства Н… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Positive significant correlations between different PI measures, for example, school-based involvement and home-based involvement (.4–.7), have been reported in many studies (Antipkina, Lyubitskaya, Nisskaya, 2018; Walker et al, 2005; Wilder, 2014). In Walker et al (2005), for example, one conclusion was that “constructs do not operate in isolation,” that is, “efforts to measure one construct may necessitate changing definitions and assessing others.”…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…Positive significant correlations between different PI measures, for example, school-based involvement and home-based involvement (.4–.7), have been reported in many studies (Antipkina, Lyubitskaya, Nisskaya, 2018; Walker et al, 2005; Wilder, 2014). In Walker et al (2005), for example, one conclusion was that “constructs do not operate in isolation,” that is, “efforts to measure one construct may necessitate changing definitions and assessing others.”…”
Section: Methodsmentioning
confidence: 82%
“…To compare the PISC-9 scale scores against traditional PI scale scores, we added into the parental questionnaire several Likert-type items on school-based and home-based PI (see Table 5). One out of four school-based PI items and four out of nine home-based PI items were kept from the adaptation of the APQ (Frick et al, 1999) and the rest were the original items that showed satisfactory characteristics on the previous wave of the iPIPS project (Antipkina, Lyubitskaya & Nisskaya, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to international research, previous researchers such as Antipkina et al (2018); Anicama et al (2018); Daniel (2015); Clifford and Göncü (2019) had all conducted a study related to this topic. In Malaysia, there are few similar studies that have been done for instance studies by (Mahamud et al, 2018;Ismail et al, 2016;Ramalingam et al, 2019;Zakaria and Salleh, 2011).…”
Section: Introductionmentioning
confidence: 99%